2021
DOI: 10.28927/sr.2021.061520
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing effect of recycled polypropylene fibers on a clayey lateritic soil in different compaction degrees

Abstract: The present research investigates the reinforcing effect of recycled polypropylene (R-PP) fibers on a compacted clayey lateritic soil in different compaction degrees. R-PP fibers of 12 mm length were mixed with the soil in the contents of 0.1 and 0.25% of soil dry weight. Unconfined compression strength tests (UCS), direct shear tests and indirect tensile strength (ITS) tests were conducted. Fibers addition showed no significate alterations in the optimum compaction parameters. The study evidenced increases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…(YASMINE and ZEINEDDINE, 2022) They indicated that 1% of polypropylene fibres (12mm and 18mm) mixed with cement content (0, 3, and 6%) and sand through the consolidated drained triaxial test increased both the cohesion and friction angle of sands. A study by (CORREIA and ROCHA, 2021) showed the effects of recycled polypropylene (R-PP) fibres on compacted clayey lateritic soil at different compaction degrees. The results of tests indicated that using fibres improved the shear stress-strain behaviour of the composites and soils compacted at different degrees of compaction.…”
Section: Introductionmentioning
confidence: 99%
“…(YASMINE and ZEINEDDINE, 2022) They indicated that 1% of polypropylene fibres (12mm and 18mm) mixed with cement content (0, 3, and 6%) and sand through the consolidated drained triaxial test increased both the cohesion and friction angle of sands. A study by (CORREIA and ROCHA, 2021) showed the effects of recycled polypropylene (R-PP) fibres on compacted clayey lateritic soil at different compaction degrees. The results of tests indicated that using fibres improved the shear stress-strain behaviour of the composites and soils compacted at different degrees of compaction.…”
Section: Introductionmentioning
confidence: 99%